RETRACTED: Combination of Tanshinone IIA and Cisplatin Inhibits Esophageal Cancer by Downregulating NF-κB/COX-2/VEGF Pathway - Liao, Xiaozhong; Gao, Ying; Liu, Jiahui; Tao, Lanting; Wang, Dongmei; Xie, Dan; Mo, Suilin (Frontiers in Oncology, 2020)
Cisplatin (DDP) represents one of the common drugs used for esophageal squamous cell carcinoma (ESCC), but side effects associated with DDP and drug resistance lead to the failure of treatment. This study aimed to understand whether tanshinone IIA (tan IIA) and DDP could generate a synergistic antitumor effect on ESCC cells. Tan IIA and DDP are demonstrated to restrain ESCC cell proliferation in a time- and dose-dependent mode. Tan IIA and DDP at a ratio of 2:1 present a synergistic effect on ESCC cells. The combination suppresses cell migration and invasion abilities, arrests the cell cycle, and causes apoptosis in HK and K180 cells. Molecular docking indicates that tan IIA and DDP could be docked into active sites with the tested proteins. In all treated groups, the expression levels of E-cadherin, β-catenin, Bax, cleaved caspase-9, P21, P27, and c-Fos were upregulated, and the expression levels of fibronectin, vimentin, Bcl-2, cyclin D1, p-Akt, p-ERK, p-JNK, P38, COX-2, VEGF, IL-6, NF-κB, and c-Jun proteins were downregulated. Among these, the combination induced the most significant difference. Our results suggest that tan IIA could be a novel treatment for combination therapy for ESCC.